Thin Films with Low Zn Content Prepared by Chemical Bath Deposition - Caijuan Tian; Jingjing Gao; Wei Li; Lianghuan Feng; Jingquan Zhang; Lili Wu (International Journal of Photoenergy)
Chemical bath deposition (CBD) was used for the growth of thin films with low Zn content. The influence of preparation conditions, such as pH, temperature, and concentration, on film properties was investigated. The chemical growth mechanism of thin films was analyzed, and optimized growth conditions for the thin films were established. The fill factor and short-circuit current were improved while was used to replace CdS as the window layer in CdTe solar cells.